Signifikansi Peran Guru Kristen Sebagai Gembala terhadap Motivasi Belajar Siswa [The Significance of the Role of Christian Teachers as Shepherds on Student Learning Motivation] - Ginting, Cindy Claudia; Christian, Grace Purnamasari (Universitas Pelita Harapan, 2023)
The teacher as a guide must be able to motivate students, not only in terms of knowledge but also guide students to understand their true purpose in life, which is to be like Christ. Based on research, 7 out of 10 children experience demotivation in learning because there is no guidance from the teacher, this shows that there are teachers who do not understand their role well. Therefore, the purpose of this study is to demonstrate the importance of the relevance of understanding Christ as the Great Shepherd. The research method used is a literature review. Christian teacher must first personally experience the shepherding of Christ so that he can understand that the students also need guidance to be able to understand their responsibilities. Christian teachers should improve the competence that is in themselves and always undergo transformation. Christian teacher must make Christ as the shepherd in his teaching and life because Christ is the authoritative God. Christian teacher should show his obedience to God in his duties and responsibilities as a guide who shepherds his students. Suggestions for future researchers are to focus more on studying how to measure a Christian teacher who has been shepherded by Christ.BAHASA INDONESIA ABSTRACT: Guru sebagai pembimbing harus dapat memotivasi siswa, tidak hanya dari segi pengetahuan tetapi juga membimbing siswa untuk memahami tujuan hidup mereka yang sebenarnya, yaitu menjadi seperti Kristus. Berdasarkan penelitian, 7 dari 10 anak mengalami demotivasi dalam belajar karena tidak ada bimbingan dari guru, hal ini menunjukkan bahwa masih ada guru yang belum memahami perannya dengan baik. Oleh karena itu, tujuan dari penelitian ini adalah untuk menunjukkan pentingnya relevansi pemahaman tentang Kristus sebagai Gembala Agung. Metode penelitian yang digunakan adalah studi literatur. Guru Kristen harus terlebih dahulu mengalami sendiri penggembalaan Kristus agar dapat memahami bahwa murid-muridnya juga membutuhkan bimbingan untuk dapat memahami tanggung jawabnya. Guru Kristen harus meningkatkan kompetensi yang ada di dalam dirinya dan selalu mengalami transformasi. Guru Kristen harus menjadikan Kristus sebagai gembala dalam pengajaran dan kehidupannya karena Kristus adalah Allah yang berotoritas. Guru agama Kristen harus menunjukkan ketaatannya kepada Tuhan dalam tugas dan tanggung jawabnya sebagai pembimbing yang menggembalakan anak didiknya. Saran untuk peneliti selanjutnya adalah untuk lebih fokus meneliti bagaimana mengukur seorang guru Kristen yang telah digembalakan oleh Kristus.